2017
DOI: 10.15405/ejsbs.210
|View full text |Cite
|
Sign up to set email alerts
|

The Mother Tongue in the Foreign Language: An Account of Russian L2 Learners’ Error Incidence on Output

Abstract: Based on Selinker's hypothesis of five psycholinguistic processes shaping interlanguage (1972), the paper focuses attention on the Russian L2-learners' overreliance on the L1 as the main factor hindering their development. The research problem is, therefore, the high incidence of L1 transfer in the spoken and written English language output of Russian learners as an EFL issue largely ignored, and the research question, how much these learners' dependence on the L1 affect their interlanguage (IL) development. T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
3
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 15 publications
0
3
0
Order By: Relevance
“…Besides warning about the domination of L1 in L2 classrooms , many researchers claim that playing an essential role in diminishing learning anxiety, the use of L1 may also help to create a more comfortable and effective learning atmosphere, particularly for shy or less-proficient L2 learners to communicate in the classroom (Rolin-Ianziti & Varshney, 2008;Nation, 2003). Furthermore, the students may have trouble understanding and participating when lessons are carried out in only target language medium since their stress ranges up and naturally, they lose their motivation (Fernandez & Korneeva, 2017;Viakinnou-Brinson et al, 2012). In this sense, as a pedagogical and instructional tool, the use of L1 is thought to serve many facilitative functions in L2 classrooms (Balam & Perez, 2017;Codina Camó & Pladevall Ballester, 2015;Levine, 2014; It has been observed that most English language classes in Turkey are conducted through the native language of learners, Turkish (Balabakgil & Mede, 2016;Kocaman &Aslan, 2018;, although the curricula developed for primary, secondary, and high schools state the opposite (MNE, 2018a(MNE, , 2018b.…”
Section: Introductionmentioning
confidence: 99%
“…Besides warning about the domination of L1 in L2 classrooms , many researchers claim that playing an essential role in diminishing learning anxiety, the use of L1 may also help to create a more comfortable and effective learning atmosphere, particularly for shy or less-proficient L2 learners to communicate in the classroom (Rolin-Ianziti & Varshney, 2008;Nation, 2003). Furthermore, the students may have trouble understanding and participating when lessons are carried out in only target language medium since their stress ranges up and naturally, they lose their motivation (Fernandez & Korneeva, 2017;Viakinnou-Brinson et al, 2012). In this sense, as a pedagogical and instructional tool, the use of L1 is thought to serve many facilitative functions in L2 classrooms (Balam & Perez, 2017;Codina Camó & Pladevall Ballester, 2015;Levine, 2014; It has been observed that most English language classes in Turkey are conducted through the native language of learners, Turkish (Balabakgil & Mede, 2016;Kocaman &Aslan, 2018;, although the curricula developed for primary, secondary, and high schools state the opposite (MNE, 2018a(MNE, , 2018b.…”
Section: Introductionmentioning
confidence: 99%
“…However, it should be pointed out that research [1], [2], [3], [4] has shown that classroom communication, the excessive use of the mother tongue, and error correction in addition to the challenges posed by new learning environments call for a change of mentality and practices in FLE practitioners and learners. These conditions imposed by, for instance, the advent of IT, the presence of the multiple language repertoires performed in international classrooms at the universities, and the resulting multicultural contact in and outside campus [5] demand proactive language policies in which not only the educational environment but also the city as whole is considered.…”
Section: Introductionmentioning
confidence: 99%
“…Forteza (2015) and Forteza and Korneeva (2017) demonstrate that interlingual interference is a major factor affecting L2 output. Dependence on the mother tongue to produce the L2 is a major factor not alien to many language learners.…”
mentioning
confidence: 99%